ENGLISH LEARNING STRATEGIES OF STUDENTS WITH A BOARDING SCHOOL BACKGROUND - Abdurrohim; IGA Widari (STKIP Paracendekia NW Sumbawa, 2024)
This study aims to investigate the English learning strategies of students both when they were still studying at Islamic boarding schools and when they studied at STKIP Paracendekia NW Sumbawa. This study used descriptive qualitative method. In collecting data, the researchers used observation and interview techniques. Data analysis used three data analysis techniques, namely; data reduction, data presentation, and conclusion drawing. The results of the study showed that there are seven English learning strategies that students used when they were still studying at Islamic boarding schools, namely memorizing vocabulary, practicing English, studying tenses, learning to make sentences, learning to read sentences, learning to make speeches, and taking English courses. On the other hand, when they were studying in college, the researchers found ten strategies used by students in learning English, namely memorizing vocabulary, practicing English, studying tenses, learning to make sentences, learning to read sentences, listening to songs and watching videos in English, making groups, English conversation, hanging out with friends who were good at English, and following English-based channels